DETERMINATION OF THE CONCEPT OF VIRTUAL PERMANENT ESTABLISHMENT IN ELECTRONIC TRANSACTIONS TO CREATE LEGAL CERTAINTY - Emelia Retno Kadarukmi, Maria (Awang Long Law Review, 2023)
This article is intended to analyze the following issues, the establishment of the concept of virtual Permanent Establishment (BUT) and the criteria required to create legal certainty in the collection of income tax on transactions via the Internet. Based on the research results, it is known that essentially e-commerce transactions are not visible (intangible). Through the definition of Article 2 paragraph (5) letter p, the Government attempts to "realize" the transaction into the real thing, so that it meets the criteria of BUT, as mentioned in the OECD in the form of "place of business". In fact, the Government in terms of determining the concept of virtual permanent establishment (BUT) and criteria required to create legal certainty in the collection of income tax on e-commerce transactions, still use the existing criteria in Article 2 paragraph (5) of Income Tax Law. However, the definition in Article 2 paragraph (5) letter p of Income Tax Law has not explained component "fixed" explicitly as required by the OECD, because it has not confirmed the limits of a certain time period, so that a server be "fixed."